2006
DOI: 10.1523/jneurosci.4818-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Disruption of an Established Morphine Conditioned Place Preference

Abstract: In human addicts, craving and relapse are frequently evoked by the recall of memories connected to a drug experience. Established memories can become labile if recalled and can then be disrupted by several interfering events and pharmacological treatments, including inhibition of protein synthesis. Thus, reactivation of mnemonic traces provides an opportunity for disrupting memories that contribute to pathological states. Here, we tested whether the memory of a drug experience can be weakened by inhibiting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
184
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(202 citation statements)
references
References 87 publications
10
184
2
3
Order By: Relevance
“…This effect is likely to be caused by the disruption of the reconsolidation of the memory (12), as the impairment of both place conditioning and withdrawal are dependent on the reactivation of mCPP. This is in agreement with the results of our previous study (14) that also demonstrated that reexperiencing morphine in a different context or in the home cage does not evoke any lability in mCPP. Furthermore, we show that the disruption of mCPP is persistent and the memory does not return after further conditioning or testing in the presence of morphine, suggesting that the disruption is not caused by state dependency.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This effect is likely to be caused by the disruption of the reconsolidation of the memory (12), as the impairment of both place conditioning and withdrawal are dependent on the reactivation of mCPP. This is in agreement with the results of our previous study (14) that also demonstrated that reexperiencing morphine in a different context or in the home cage does not evoke any lability in mCPP. Furthermore, we show that the disruption of mCPP is persistent and the memory does not return after further conditioning or testing in the presence of morphine, suggesting that the disruption is not caused by state dependency.…”
Section: Discussionsupporting
confidence: 93%
“…Given the relevant contribution of the contextual representation in both mCPP and withdrawal, we tested whether the hippocampus, a brain region known to process contextual and place memories (20), including mCPP, is involved in linking memories to withdrawal. Dorsal or complete hippocampal lesions impair rat mCPP (21), and we have previously shown that an injection of the protein synthesis inhibitor anisomycin into the dorsal hippocampus following mCPP reactivation persistently disrupts an established mCPP memory (14). Here we tested whether blocking protein synthesis in the dorsal hippocampus affects the link between mCPP and withdrawal evoked as in the previous experiments.…”
Section: Drug Conditioning Is Required For Linking Motivational Withdmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition to amnesias produced by anisomycin injections into the amygdala, as above, anisomycin also impairs memory when administered to other memory systems, including the hippocampus, where anisomycin impairs inhibitory avoidance memory (Quevedo et al 1999;Debiec et al 2002;Milekic et al 2006). The present study extends the prior findings ) in several respects.…”
mentioning
confidence: 93%